The Impact of the Corona Crisis on the Worldwide Stock Markets: An Empirical Analysis with Cross National Event Study Approach - Fischer, Annika; Opala, Noel; Reuse, Svend; Svoboda, Martin (International Journal of Economics and Financial Issues, 2022)
The Corona Crisis led to a high drawdown in the stock markets in the whole world in March 2020. After that, infection rates, incidences, and dead people were published by many countries. Based on 11 stock price indices analyses according to volatility and correlation, we can conclude that only one event seems to be substantially affected by a Corona-related event not tied to specific countries. Therefore, in times of crisis, stock indices correlate highly positively. This leads us to a second step to our central research question: Do Corona dates significantly impact the stock price development? Therefore, we analyzed several events in Germany and the US with the event study approach. The main result is that only the March 2020 event significantly impacts the volatility and the returns. The following bad news but also the good news do not have any influence on the share prices and do not lead to abnormal returns. For example, the first approval of vaccinations had no apparent effect on the stock market, which was reflected in price movements comparable to those during the initial Lockdown.